ANALISIS PERBANDINGAN PERFORMA VIRTUALISASI SERVER MENGGUNAKAN VMWARE ESXI, ORACLE VIRTUAL BOX, VMWARE WORKSTATION 16 DAN PROXMOX - Ridho Akbar Nuryadin; Ramadhani, Tarisa A.; Karaman, Jamilah; Reza, Muhammad (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
In the era of advancing digitization, server infrastructure plays a key role in the development of applications and web services. To effectively and efficiently manage and develop virtualized servers, server virtualization techniques can be employed. There are several virtualization platforms available, such as VMware Workstation 16, VMware vSphere (ESXi), Oracle VirtualBox, and Proxmox, each with their own strengths and weaknesses. The objective of this research is to analyze the performance of these four virtualization platforms in developing and managing virtualized servers used for web services, taking into consideration response time, throughput, CPU performance, storage performance, and RAM performance. Experimental methods were used to test these four platforms and measure CPU performance, RAM performance, disk performance, throughput, and response time using Moodle benchmark. The data was then analyzed to draw conclusions about the performance of each platform. The research results show that VMware vSphere ESXi and Proxmox have better CPU performance and response time when handling multiple virtual machines, and are more efficient in disk and memory usage compared to VMware Workstation 16 and Oracle VirtualBox. Significant differences in data transfer speed were found among the four platforms. Overall, VMware vSphere ESXi and Proxmox can be considered better choices for running web servers.